2013
DOI: 10.1242/jeb.070482
|View full text |Cite
|
Sign up to set email alerts
|

Environmental interaction influences muscle activation strategy during sand-swimming in the sandfish lizard Scincus scincus

Abstract: SUMMARYAnimals like the sandfish lizard (Scincus scincus) that live in desert sand locomote on and within a granular medium whose resistance to intrusion is dominated by frictional forces. Recent kinematic studies revealed that the sandfish utilizes a wave of body undulation during swimming. Models predict that a particular combination of wave amplitude and wavelength yields maximum speed for a given frequency, and experiments have suggested that the sandfish targets this kinematic waveform. To investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 74 publications
1
69
0
1
Order By: Relevance
“…Data sets were analyzed from previous work (see Sharpe et al, 2013). All experimental procedures were conducted in accordance with the Georgia Institute of Technology IACUC protocol number (A08012) and Radiation Safety protocol (X-272).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data sets were analyzed from previous work (see Sharpe et al, 2013). All experimental procedures were conducted in accordance with the Georgia Institute of Technology IACUC protocol number (A08012) and Radiation Safety protocol (X-272).…”
Section: Methodsmentioning
confidence: 99%
“…7A) (Gravish et al, 2010;Li et al, 2009;Sharpe et al, 2013). The bed (22.9×40.6 cm 2 ) was filled with glass particles (diameter=0.27±0.04 mm and density=2.5 g cm -3…”
Section: Substrate Preparation and Trial Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas these turns constitute a form of internal perturbation, further testing of this hypothesized template should include how the animal responds to external perturbations (22) (such as obstacles) as well as measurements of the underlying neural controls predicted by template control (e.g., as in sand swimming in ref. 23). Coupling such studies to further investigation of the robot could help explain why the sidewinder rattlesnake moves effectively on granular media, whereas its close relatives do not (9), and establish these organisms as an ideal model system for two-wave template locomotion.…”
Section: Significancementioning
confidence: 99%
“…Other sand-swimming reptiles, such as the sandfish (Scincus scincus), the Kenyan sand boa (Eryx colubrinus), and the Saharan sand viper (Cerastes cerastes), produce biogenic structures like those of Chalcides ocellatus in similar sediment (Young and Morain, 2003;Hembree and Hasiotis, 2007;Baumgartner et al, 2008). Studies of the mechanics of sand-swimming locomotion have primarily involved the sandfish whose method of sand swimming is nearly identical to that of C. ocellatus (Baumgartner et al, 2008;Maladen et al, 2009;Sharpe et al, 2013). These studies have shown that the burrowing behavior of S. scincus is similar to that of C. ocellatus.…”
Section: Comparison With Other Extant Sand-swimmingmentioning
confidence: 99%